DEVELOPMENT OF PHYSICS LEARNING MEDIA BASED ANDROID USING CODULAR TO IMPROVE STUDENT LEARNING OUTCOMES ON TEMPERATURE AND HEAT MATERIAL - Ghillanda, Chairin; Simamora, Pintor (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
Research was conducted due to the lack of interesting learning media, making students' interest in physics subjects to study physics low and resulting in unsatisfactory student learning outcomes. This research aims to develop android-based learning media using kodular as a learning media to improve student learning outcomes on temperature, expansion and heat material for high school class XI. This research is a Research & Development (R & D) study using the ADDIE model which consists of stages (Analyze, Design, Development, Implementation and Evaluation). The subjects of this research were students of class XI SMA The results of material expert validity have a percentage of 91.11% with a very valid category and media expert validity has a percentage of 90% with a very valid category. The results of practicality by students in small groups of 87.95% (very practical), medium groups of 85.54% and limited groups of 94.75% (very practical) and in the effectiveness test obtained the results of the gain score of the difference between the pretest and protest scores showed an average in the small group of 0.7707, medium group 0.7777 while in the limited group of 0.8348 in the high category. Based on this information, it is concluded that the android-based student learning media using codular to improve student learning outcomes on temperature, expansion and heat material at SMAN 5 Medan developed by researchers get results that are feasible to use with valid, very practical and effective categories. ABSTRAK Penelitian dilakukan karena kurangnya media pembelajaran yang menarik menyebabkan minat siswa terhadap mata pelajaran fisika untuk mempelajari fisika rendah dan mengakibatkan hasil belajar siswa kurang memuaskan. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis android dengan menggunakan kodular sebagai media pembelajaran untuk meningkatkan hasil belajar siswa pada materi suhu, muai dan kalor SMA kelas XI. Penelitian ini merupakan penelitian Research & Development (R&D) dengan menggunakan model ADDIE yang terdiri dari tahapan (Analisis, Desain, Pengembangan, Implementasi dan Evaluasi). Subyek penelitian ini adalah siswa kelas XI SMA. Hasil validitas ahli materi mempunyai persentase sebesar 91,11% dengan kategori sangat valid dan validitas ahli media memiliki persentase sebesar 90% dengan kategori sangat valid. Hasil praktikalitas siswa pada kelompok kecil sebesar 87,95% (sangat praktis), kelompok sedang sebesar 85,54% dan kelompok terbatas sebesar 94,75% (sangat praktis) dan pada uji keefektifan diperoleh hasil gain score selisih pretest dan skor protes menunjukkan rata-rata pada kelompok kecil sebesar 0,7707, kelompok sedang sebesar 0,7777 sedangkan pada kelompok terbatas sebesar 0,8348 dengan kategori tinggi. Berdasarkan informasi tersebut disimpulkan bahwa media pembelajaran siswa berbasis android menggunakan codular untuk meningkatkan hasil belajar siswa pada materi suhu, muai dan kalor di SMAN 5 Medan yang dikembangkan peneliti mendapatkan hasil yang layak digunakan dengan valid, sangat praktis dan kategori efektif.